PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI PEMBELAJARAN BERBASIS PROYEK BERBANTUAN IMAGE DI SEKOLAH DASAR - Melia Andari; Hamzan (Walada: Journal of Primary Education, 2023)
This research aims to improve students' critical thinking skills using the Project Basead Learning Model in social science learning in elementary schools. The project-based learning model directs students to complete it directly and places responsibility on students during the learning process by generating critical ideas. It is studied using classroom action research with two cycles, each consisting of two meetings with four stages. Continuous, namely planning, implementation, observation, and reflection. The data collected includes teacher activities, student activities, and data that can provide conclusions about critical thinking skills. The research results show that project-based learning can improve the critical thinking skills of fifth-grade students in elementary schools; this is proven by calculating the first cycle classical completeness score of 69%. Moreover, there was an increase of 27.59% to 97%. This success was supported by changes and improvements to the learning process following the reflection results in the previous cycle.